Counseling and Making Environment Friendly Cleansing Using Fruit and Flower Extractsin The Framework of Increasing The Welfare of Teachers and Preparing Independent Entrepreneurship For SMA-IT Studentsriyadhussholihiin Islamic Boarding School- Cimanuk-Pandegelang - I G A Arwati; Hari Setiyawati; Gian Villany Golwa; Wiwit Suprihatiningsih; Erna Setiany; Yudhi Herliansyah; Siti Choiriah; Suharmadi Suharmadi; Safira Safira; Sri Purwaningsih; Puji Rahayu; Riri Pratiwi (International Journal Of Community Service, 2023)
This community service is carried out in the context of foreign cooperation where the partner is Professor Dr. Yusliza Mohd Yusoff from Universiti Malaysia Terengganu (UMT). We carry out this community service activity with the theme "Counseling and Making Environmentally Friendly Cleaners Using Lime Extract In the Context of Improving the Welfare of Teachers and Preparing Independent Entrepreneurship for SMA-IT Students at the Riyadhussholihiin-Cimanuk- Pandegelang Islamic Boarding School.” The targets in this activity were teachers and students of class XII SMA-IT at the Riyadhussholihiin-Cimanuk-Pandegelang Islamic Boarding School. They were given training and directly practiced making eco-friendly cleaners using lily extract. The PPM team will also provide assistance until the product can actually be marketed. The initial target for this product is to be used alone and sold to the laundry unit at the Riyadhussholihiin Islamic Boarding school. The next target will be sold to people outside the Riyadhussholihiin Islamic Boarding School. Activities will begin in February 2023 (In Syaa Allah) and end in June or July 2023. However, assistance will continue to be carried out to maintain the continuity of these activities.Professor Dr. Yusliza Mohd Yusoff s as a partner will inspect the field directly or monitor through the Vicon Zoom Meeting. The results of these activities are in the form of increased welfare for teachers obtained from the sale of environmentally friendly cleaning products. Also for students after graduation they can do entrepreneurship to make these products, both students who continue their studies and those who do not continue their studies can still do entrepreneurship. Evaluation can be done by monitoring the location after the community service implementation period is over. Assistance will continue to be carried out to maintain the continuity of the production and sales process.